2021
DOI: 10.21203/rs.3.rs-845748/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Berberine Inhibits FoxM1 Dependent Transcriptional Regulation of POLE2 and Interferes with the Survival of Lung Adenocarcinoma

Abstract: Background:Berberine is one of the most interesting and promising natural anticancer drugs. POLE2 is involved in many cellular functions such as DNA replication and is highly expressed in a variety of cancers. However, the specific molecular mechanism of berberine interfering with POLE2 expression in lung adenocarcinoma (LUAD) is still unknown to a great extent.Method:The KEGG database (Release 91.0) and Gene Ontology (GO) category database were used for functional annotation of differentially expressed genes … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…[46] Berberine can effectively inhibit the proliferation and migration of LUAD. [47] The study found that berberine blocked DNA replication in LUAD cells by down-regulating DNA polymerase epsilon 2 and DNA primase subunit 1 in LUAD cells. At the same time, Berberine has a down-regulating effect on the main gene expression biomarker (forkhead box M1) that can reflect the poor prognosis of pan-cancer, [47] which indicates that berberine has a good inhibitory effect on the development of LUAD cells throughout the cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[46] Berberine can effectively inhibit the proliferation and migration of LUAD. [47] The study found that berberine blocked DNA replication in LUAD cells by down-regulating DNA polymerase epsilon 2 and DNA primase subunit 1 in LUAD cells. At the same time, Berberine has a down-regulating effect on the main gene expression biomarker (forkhead box M1) that can reflect the poor prognosis of pan-cancer, [47] which indicates that berberine has a good inhibitory effect on the development of LUAD cells throughout the cycle.…”
Section: Discussionmentioning
confidence: 99%
“…[47] The study found that berberine blocked DNA replication in LUAD cells by down-regulating DNA polymerase epsilon 2 and DNA primase subunit 1 in LUAD cells. At the same time, Berberine has a down-regulating effect on the main gene expression biomarker (forkhead box M1) that can reflect the poor prognosis of pan-cancer, [47] which indicates that berberine has a good inhibitory effect on the development of LUAD cells throughout the cycle. Palmatine is a class of isoquinoline alkaloids with highly effective biological activity and good water solubility and has shown a good effect in promoting apoptosis of adenocarcinoma cells in previous studies.…”
Section: Discussionmentioning
confidence: 99%